Determining the Preferences Towards Insurance Products among Mall Goers of SM Manila - Anada, Maria Jella I.; Antonio, Carl Jason R.; Arsenal, John Carl S.; Fayen, Veronica Grade D.; Lopez, Joyce Krisneza P. and Tambio, Cyrril Mae C. 4 0 16; 5
ABSTRACT: Insurance Industry was known by people for the reason that they realized that it reduce risk and it secures individuals for future needs. Insurance Commission was the regulatory body of insurance including life, non-life and pre-need. Life insurance can cover for a period of more than a year; it pays out a certain amount of money to the insured upon certain event. There are four main products of life insurance including whole life, limited pay whole life, term and variable life insurance. Furthermore, non-life insurance also called as general insurance is a policy that protects losses and damages of individuals other than covered by life insurance. The main products on non-life are fire, motor and personal accident. Lastly, the pre-need that provide for future services or payment of money for the future needs having including educational, pension and memorial plans. The purpose of the study was to determine the least and most preferred insurance products of individuals, as well as to analyse the significant differences among the preferences of the mall goers within SM City Manila according to the demographic profile. The study also aimed to find out the demographic profile of the mall goers within SM City Manila as to age, gender, civil status, educational attainment, work/profession, and work industry and income level. Also, the spending priorities of individuals based on their lifestyle. More importantly, the study was required to analyse and find out the least and most preferred products of an individual and the significant differences among the preferences according to the demographic profile of individuals. A qualitative research was used because it involves data collection and analysis. The study was conducted on SM City of Manila during the time from 5:00 P.M. to 8:00 PM wherein many people were entering the shopping mall since in it was peak hours. By averaging the number of individuals entering the shopping mall within the said span of time, it came up with a total population of 2,720. In order to determine the sample size, the researchers used the Slovin's formula using the confidence level of 95% and it resulted to 349 sample size. Frequency and percentage distribution will be the tool used in tabulating the demographic profile of the respondents. To determine the ranking of the given spending habits of the respondents, weighted mean was used. The spending priority which has the lowest weighted mean in each will be the first in the rank and so forth. To determine the most preferred and least preferred products of life, non-life and pre need of the respondents, the weighted average mean was used. Based on the data gathered, the older an individual the more they were engaged in insurance policies than the younger ones. Married persons prefer pre-need plans such as educational plans to secure the future of their children. The higher educational attainment, the more knowledgeable a person is with regards to the value of insurance and of its products. A person's monthly income influences their inclination towards insurance products. Those with a large income are more capable in getting and prioritizing insurance than those with an average or miniature income. All outcomes in this study may be used by the insurance industry, agents or companies, for developing marketing strategy designed for prospective clients. The individuals who will engage in insurance products shall be aware of what they will go through and be knowledgeable enough not only in insurance but also for proper savings.
Thesis: (BSBA major in Treasury Management) - Pamantasan ng Lungsod ng Maynila, 2014.
Keywords: 2 -- 0; 6; 20; 20; 2